The Influence of Company Size, Company Growth, and Financing Policy on Company Value (Study on Financial Sector Companies Listed on the Indonesia Stock Exchange for the Period 2019 - 2023) - Putraina, Khalid; Dwi Urip Wardoyo (LP2M IAIN Palopo, 2025)
This study aims to analyze the effect of company size, company growth, and financing policy on company value in financial sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Company value in this study is measured using Price to Book Value (PBV). The research method used is a quantitative method with a descriptive and verification approach. The data used is secondary data obtained from the annual financial reports of financial sector companies. The analysis technique used is panel data regression. The results of the study show that simultaneously company size, company growth, and financing policy have a significant effect on company value. Partially, company size and financing policy have a significant effect on company value, while company growth does not have a significant effect. These findings are expected to be a reference for investors and company managers in making strategic decisions related to increasing company value.